Is Tax Administration "Ectopic"? Assessment, Interpretation, Adjudication and Application: The Roles of the Commissioner of Inland Revenue - Griffiths, Shelley (Victoria University of Wellington Law Review, 2022)
John Prebble described the dislocation of the premises of tax law from their underlying facts as an example of "ectopia". This article suggests that the same phenomenon may apply to tax administration and the tax system more generally. The Commissioner’s dual roles of adjudication and administration are not only difficult to elucidate from the unwieldy and outdated structure of the Tax Administration Act. More importantly, they exhibit a (perhaps irreconcilable) tension between two competing goals. On the one hand, the Commissioner has a duty to arrive at a correct interpretation of tax law and its application of the facts. On the other, the Commissioner is required to exercise a political function, prioritising expenditure and ensuring efficient outcomes. Both goals ultimately lead to functions properly carried out by the courts – statutory interpretation and application; and review of administrative processes of decision-making. However, the way the Commissioner exercises these powers is divorced from the way the courts resolve similar questions – a problem which is exemplified when considering the Commissioner’s power to amend a taxpayer’s assessment of income to ensure its "correctness". There is therefore a risk that the interpretive community surrounding the tax system is increasingly becoming divorced from the rest of the common law and vulnerable to capture by its own self-referring frames of reference.